Pun Intended? A Discourse Analysis of Sinhala-English Bilingual Puns on Social Media - Wijesiriwardana, S. (University of Jaffna, 2025)
Within the postcolonial context of Sri Lanka, English plays a vital role in moulding the nation’s linguistic discourse. Sri Lankan English has been established as a variety, and its developmental trajectory can be grounded in the theoretical framework of Postcolonial Englishes. Further, with globalisation and the dissemination of internet, the hegemonic grip held by English in Sri Lanka is further strengthened as English has seemingly become the dominant lingua franca, especially in social media. In the Sri Lankan context, the sociolinguistic landscape of social media platforms is characterized by the dynamic interplay between English and local languages, namely Sinhala, fostering a space for linguistic creativity. Out of the myriad varieties of creative linguistic constructions- such as lyrics and taglines in advertisements- bilingual puns in the form of memes are the foci of this study. A pun is a creative take on language where wordplay is used to evoke humour, and to grasp the meaning of a pun, the context is of vital importance. Bilingual puns are a result of blending, code-mixing and code-shifting, and these linguistic processes are vital features of nativisation of English, in a Postcolonial Englishes perspective. Therefore, this study aims to present a sociolinguistic analysis of the features of Sinhala and English bilingual puns present on Facebook and Instagram. Memes with bilingual puns were selected from chosen Facebook and Instagram pages. By utilising Norman Fairclough’s Critical Discourse Analysis, these memes were analysed to identify their linguistic features and their context and culture-specific nature. Additionally, it was deduced that blending was the most prevalent linguistic feature in the creation of bilingual puns. Therefore, this study contributes to the study of morpho-syntactic features of Sri Lankan English and Sinhala-English bilingual puns.
Keywords: Bilingual puns; Linguistic creativity; Nativisation; Socio linguistics; Sri Lankan English